Draft Genome Sequence of Mycobacterium tuberculosis Strain MT43, a Representative of the Manu2 Genotype - Aboubaker Osman, Djaltou (Genome Announc, 2015)
We announce the draft genome sequence of Mycobacterium tuberculosis strain MT43, isolated from a pulmonary form of tuberculosis in French Polynesia. Analyzing its 4,145,007-bp, 65.17% G+C chromosome confirmed a fully antibiotic-susceptible Manu2 spoligotype.